Magnetic Properties and Redox State of Impact Glasses: A Review and New Case Studies from Siberia - Pierre Rochette; Natalia S. Bezaeva; Andrei Kosterov; Jérôme Gattacceca; Victor L. Masaitis; Dmitry D. Badyukov; Gabriele Giuli; Giovani Orazio Lepore; Pierre Beck (Geosciences, 2019)
High velocity impacts produce melts that solidify as ejected or in-situ glasses. We provide a review of their peculiar magnetic properties, as well as a new detailed study of four glasses from Siberia: El’gygytgyn, Popigai, urengoites, and South-Ural glass (on a total of 24 different craters or strewn-fields). Two types of behavior appear: 1) purely paramagnetic with ferromagnetic impurities at most of the order of 10 ppm; this corresponds to the five tektite strewn-fields (including the new one from Belize), urengoites, and Darwin glass. Oxidation state, based in particular on X-ray spectroscopy, is mostly restricted to Fe2+; 2) variable and up to strong ferromagnetic component, up to the 1 wt % range, mostly due to substituted magnetite often in superparamagnetic state. Accordingly, bulk oxidation state is intermediate between Fe2+ and Fe3+, although metallic iron, hematite, and pyrrhotite are sometimes encountered. Various applications of these magnetic properties are reviewed in the field of paleomagnetism, magnetic anomalies, recognition of glass origin, and formation processes.